Brain-derived neurotrophic factor plasma levels are associated with mortality in critically ill patients even in the absence of brain injury - Ritter, Cristiane (BioMed Central, 2012)
INTRODUCTION: Because of its relevance to the functioning of the central nervous system, brain-derived neurotrophic factor (BDNF) has been implicated in the pathogenesis of different neuropsychiatric diseases. Whether the BDNF level can be a marker of brain dysfunction and thus predict mortality in critically ill patients is not known. Thus we aimed to determine whether the plasma levels of BDNF are associated with morbidity and mortality in critically ill patients. METHODS: Healthy volunteers (n = 40) and consecutive patients older than 18 years (n = 76) admitted for more than 24 hours in an Intensive Care Unit (ICU) in a University hospital between July and October 2010 were included in the present study. First blood samples were collected within 12 hours of enrollment (D0), and a second sample, 48 hours after (D2) for determination of plasma BDNF levels. The relation between BDNF levels and mortality was the primary outcome. The secondary outcomes were the relation between BDNF levels and delirium and coma-free days (DCFD) and ICU and hospital length of stay (LOS). RESULTS: Admission plasma levels of BDNF were higher in ICU patients when compared with healthy volunteers (1,536 (962) versus 6,565 (2,838) pg/ml). The mean BDNF D2 was significantly lower in nonsurvivor patients (5,865 (2,662) versus 6,741 (2,356) pg/ml). After adjusting for covariates, BDNF levels, the need for mechanical ventilation, and sepsis were associated with mortality. Even in patients without clinically detectable brain dysfunction, lower BDNF D2 levels were associated with mortality. BDNF D2 had a mild correlation to DCFD (r = 0.44), but not to ICU and hospital LOS. In addition, plasma BDNF did not correlate to different plasma cytokines and platelets levels. CONCLUSIONS: The plasma levels of BDNF were independently associated with mortality, even in the absence of clinically detectable brain dysfunction.